Mechanical Design of an Exoskeleton for Wrist Rehabilitation - Paccori Gonzales, Jhon Klenin (2025)
The mechanical design of an exoskeleton for wrist rehabilitation is an innovative solution improve the effectiveness of therapy and the quality of life of patients. This scientific paper presents the mechanical design process of the ergonomic and lightweight exoskeleton, as well as the results obtained in performance and efficacy tests in wrist rehabilitation. The exoskeleton consists of a mechanical structure that is attached to the patient´s hand by means of an adhesive velcro and is equipped with two servomotors which allow a precise and controlled movement. The test results demonstrate the main mobilities and sufficient resistance of the exoskeleton during the established rehabilitation exercises. It also features precise turning angles with no margino f error. This mechanical design can be used in hospitals, clinics and even at home, supervised by a remote specialist.